The proton Nuclear Magnetic Resonance spin-lattice relaxation rate of some hydrated synthetic and natural sands - Bray, Christina L.; Bryant, Robert G.; Cox, M. J.; Ferrante, Gianni; Goddard, Y.; Sur, Sandip; Hornack, Joseph P. (Diffusion Fundamentals, 2009)
The proton nuclear magnetic resonance (NMR) spin-lattice relaxation rate (R1) of hydrated sands is often used to determine porosity characteristics of near-surface aquifers using magnetic resonance sounding. Large variations in R1 have been reported in laboratory measurements on hydrated sands. To understand these variations, the R1 values of several fully hydrated sands were studied as a function of grain diameter (d) and magnetic field strength (BB0). We conclude the variations are a consequence of trace paramagnetic metals in the sand grains. R1 values from magnetic resonance sounding data should not be used to predict void size in aquifers unless the exact chemical composition of the grains is known.